Association of Musculoskeletal Indexes With 1-Year Outcomes After ≥ 7 Days of Mechanical VentilationTake-Home Points - Hannah Wozniak, MD; Erminio Santangelo; Micheal McInnis; Laura Dragoi; Priscila Robles; Leslie M. Chu; Andrea Matte; Margaret S. Herridge; Margaret S. Herridge; Leslie M. Chu; Andrea Matte; George Tomlinson; et al. (CHEST Critical Care)
Background: In critically ill patients, musculoskeletal indexes have been associated with short-term outcomes such as in-hospital mortality and discharge disposition. Their influence on long-term outcomes in chronically critically ill patients remains unclear. Research Question: Does an association exist between musculoskeletal indexes and 1-year mortality in chronically critically ill patients? Are these indexes also associated with 7-day post-ICU functional independence measure (FIM) and discharge disposition? Study Design and Methods: This study used the Canadian Outcomes and Needs Assessment in Intensive Care Unit (ICU) Survivors of Prolonged Mechanical Ventilation and Their Caregivers (RECOVER) phase 1 cohort of patients requiring mechanical ventilation for ≥ 7 days. Patients who underwent abdominal CT imaging within the first 14 days of ICU admission were included. Skeletal muscle index (SMI), psoas muscle index (PMI), and trabecular bone density (BD) were measured at the L3 vertebral level. Multivariable logistic regression assessed the association between each index and 1-year mortality; multivariable linear regression assessed the association with 7-day post-ICU FIM. A Kruskal-Wallis H test compared musculoskeletal indexes across 4 discharge disposition groups. Results: One hundred patients were included; the median age was 57 years (interquartile range [IQR], 45-65 years), and 43% were female. Those who did not survive by 1 year showed lower musculoskeletal indexes than survivors: median SMI, 28.8 cm2/m2 (IQR, 22-34 cm2/m2) vs 33.5 cm2/m2 (IQR, 25.7-44.1 cm2/m2; P = .03); median PMI, 3.3 cm2/m2 (IQR, 2.5-4.5 cm2/m2) vs 4 cm2/m2 (IQR, 3.2-5.6 cm2/m2; P = .02); and median BD, 131 Hounsfield units (HU; IQR, 100-196 HU) vs 175 HU (IQR, 131-220 HU; P < .01). Lower SMI (OR per 10-unit decrease, 2.00; 95% CI, 1.21-3.33; P < .01), PMI (OR per 1-unit decrease, 1.54; 95% CI, 1.06-2.23; P = .02), and BD (OR per 10-unit decrease, 1.10; 95% CI, 1.01-1.20; P = .05) were associated significantly with 1-year mortality. No significant association was found between musculoskeletal indexes and FIM 7 days after ICU stay. Significant differences in SMI were found across discharge groups (χ2 (3) = 7.882; P = .048). Interpretation: The results of this study suggest that decreased musculoskeletal indexes are associated with 1-year mortality in chronically critically ill patients. These findings may help to inform clinical decision-making. Clinical Trial Registration: ClinicalTrials.gov; No.: NCT00896220; URL: www.clinicaltrials.gov